2009
DOI: 10.1186/1471-2318-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an evidence-based guidance on the reduction of physical restraints in nursing homes: a cluster-randomised controlled trial [ISRCTN34974819]

Abstract: BackgroundPhysical restraints are regularly applied in German nursing homes. Their frequency varies substantially between centres. Beneficial effects of physical restraints have not been proven, however, observational studies and case reports suggest various adverse effects. We developed an evidence-based guidance on this topic. The present study evaluates the clinical efficacy and safety of an intervention programme based on this guidance aimed to reduce physical restraints and minimise centre variations.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…One unpublished study (Koczy et al. 2005) and two ongoing studies were identified (Haut et al. 2009, Gulpers et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One unpublished study (Koczy et al. 2005) and two ongoing studies were identified (Haut et al. 2009, Gulpers et al.…”
Section: Resultsmentioning
confidence: 99%
“…Two further studies were identified through other sources (Pellfolk et al 2010, Testad et al 2010. One unpublished study (Koczy et al 2005) and two ongoing studies were identified (Haut et al 2009, Gulpers et al 2010. The final Cochrane review analysed five studies.…”
Section: Resultsmentioning
confidence: 99%
“…We compared our review results with the Cochrane Review ' Interventions for preventing falls in older people living in the community ' (Gillespie 2012), and identified six other systematic reviews incorporating meta-analyses (Chan 2015; Le Blanc 2015; Sherrington 2017; Silva 2013; Stubbs 2015; Vlaeyen 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Vlaeyen 2015 included 13 randomised controlled trials of fall-prevention programmes conducted in nursing homes. The authors found no significant effect of the interventions overall on the number of falls (10 studies) or risk of falling (six studies).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, restraint use promoted passivity [14]. Reduced psychological wellbeing has also been observed [15]. Sullivan-Marx (1995) found withdrawal, regression and denial to be adverse responses to routine restraint use in older adults [16].…”
Section: Adverse Effects Of Restraint Usementioning
confidence: 99%